Analisis Tantangan dalam Penerapan Teknik Membaca Intensif pada Kegiatan Membaca Jurnal Akademik - Zena Ariqoh; Navyola Yussi Prastika; Natasya Dwi Aprilia; Silvianita Nur Azizah; Mia Riani; Trinil Dwi Turistiani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to identify the challenges students face in applying intensive reading techniques when reading academic journals. A qualitative descriptive approach was used involving 29 students, consisting of 20 questionnaire respondents and 9 interview participants. Data were collected through open-ended questionnaires and interviews to explore students’ experiences in understanding scientific articles. The data were analyzed through grouping, reduction, and interpretation based on emerging themes.The findings show that most students have applied intensive reading techniques to examine journal content in depth, particularly in identifying main ideas, understanding authors’ arguments, and analyzing research data. However, several challenges were identified, including limited time due to academic workload, difficulty understanding scientific terms and concepts, lengthy journal articles, and reduced concentration during reading. These obstacles often require students to spend more time achieving a comprehensive understanding of journal content.To address these difficulties, students employed various strategies, such as rereading challenging sections, searching for definitions from additional sources, taking brief notes, and comparing information with supporting references. Overall, the findings indicate that intensive reading contributes to the development of academic literacy skills, although its effectiveness is influenced by technical and cognitive factors.